Nonnative tree invaders lead to declines in native tree species richness - Yunpeng Liu; Samuel M. Scheiner; J. Aaron Hogan; Matthew B. Thomas; Pamela S. Soltis; Robert P. Guralnick; Douglas E. Soltis; Jeremy W. Lichstein (Proceedings of the National Academy of Sciences, 2025)
Biological invasions are profoundly altering Earth’s ecosystems, but generalities about the effects of nonnative species on the diversity and productivity of native communities have been elusive. This lack of generality may reflect the limited spatial and temporal extents of most previous studies. Using >5 million tree measurements across eastern US forests from 1995 to 2023, we quantified temporal trends in tree diversity and biomass. We then analyzed community-level changes in native tree diversity and biomass in relation to nonnative tree invasion and native species colonization. Across the entire eastern United States, native tree species richness decreased over time in plots where nonnatives occurred, whereas nonnative species richness and the biomass of both natives and nonnatives increased over time. At the community scale, native richness tended to decline following nonnative invasion, whereas native biomass and richness-independent measures of trait and phylogenetic diversity tended to remain stable. These patterns can be explained by the rarity of the displaced native species and their functional and phylogenetic similarity to native species that survived nonnative invasions. In contrast, native survivors tended to be functionally distinct from nonnative invaders, suggesting an important role for niche partitioning in community dynamics. Colonization by previously absent native species was associated with an increase in native richness (beyond the addition of native colonizers), which contrasts with declines in native richness that tended to follow nonnative invasion. These results suggest a causal role for nonnative species in the native richness decline of invaded communities.